Tinjauan Yuridis terhadap Perceraian Disebabkan Kemandulan Isteri dalam Perkawinan - Ritonga, Deby Syahputri; Daulay, Agus Salim (Jurnal Ilmiah Penegakan Hukum, 2017)
Juridical review Against Infertility Caused Divorce Wife In MarriageMany people crave marriage, both men and women. A married couple who are not harmonious because they cannot be trusted from marriage with divorce. This study uses a type of normative legal research, a scientific research procedure to find truth based on legal scientific logic from the normative side. The characteristics of this research are descriptive, namely research carried out with the main objective, objectively determining objectives. The technique of collecting data in it is by collecting legal materials consisting of basic materials, legal materials and non-legal materials. Children in a family are very helpful if there is no family that can produce offspring, nor is there a family with a divorce caused by one party. Various reasons can be used as reasons for divorce, one of which is a continuous disp